Research handbook on EU energy law and policy - Leal-Arcas, Rafael; Wouters, Jan, 1964- (Research handbooks in European law, 2017)
This authoritative Research Handbook presents, for the first time, a comprehensive overview of the most important research and latest trends in EU energy law and policy. It offers high-quality original contributions that provide state-of-the-art research in this rapidly evolving area, situated in the broader context of international economic law and governance. The Research Handbook covers the full breadth of topics and developments in the EU's law and policy regarding energy, fully acknowledging the multifaceted nature of this vast arena. It is divided into four broad thematic areas of EU energy law and policy: 1) institutional aspects; 2) external aspects; 3) economic, social and legal aspects; and 4) environmental and technological aspects. Expert contributors also present a future research agenda in these four areas and identify emerging themes with substantial potential for further research in years to come. Timely and engaging, the Research Handbook on EU Energy Law and Policy will be an indispensable reference point for academics, students, lawyers, economists, policymakers and think tanks in the field. It will also be of interest to those operating in other energy-related disciplines.